Bioanalytical separations - Wilson, Ian D. (Handbook of analytical separations, 2003)
Bioanalytical Separations is volume 4 of the multi-volume series, Handbook of Analytical Separations, providing reviews of analytical separation methods and techniques used for the determination of analytes across a whole range of applications. The theme for this volume is bioanalysis, in this case specifically meaning the analysis of drugs and their metabolites in biological fluids. - Discusses new developments in instrumentation and methods of analyzing drugs and their metabolites in biological fluids - Provides guidance to the different methods, their relative value to the user, and the advantages and pitfalls of their use - Future trends are identified, in terms of the potential impact of new technologies.